PENDAMPINGAN PEMBUATAN KEMASAN DAN IKLAN KULINER KHAS DAERAH PRODUK PEDAGANG KECIL DI KECAMATAN ILIR BARAT I PALEMBANG - Muhammad Nadjmuddin; Sunani Sunani; Yusri Yusri; Indri Ariyanti; Fitria Wulandari; Triana Putri; Winda Permata Putri (Politeknik Negeri Sriwijaya, 2022)
Abstract Palembang is famous for not only songket clothes but also specific food such as pempek and mie celor (stemmed noodles). Many Small Micro Medium Enterprises (SMMEs) need coaching in order to succeed in their busines. They do not have sufficient financing sources and strategies to grow and face fierce business competition. One of necessary assistances is helping them improve their packaging and develop persuasive advertisements through social media promotion. The two SMMEs, Pempek Cek Eha and Mie Celor Ujuk Imam 26, are located in Kecamatan Ilir Barat I Palembang. This community service activity was carried out to help fostered the SMMEs to survive in their current situation through product packaging and online advertisement development. Good product packaging can be used for online advertising activities, which are expected to increase sales during the pandemic. Their previous packaging seemed to be careless and unattractive. Their promotions and sales were managed conventionally through direct face to face and limited online transactions, as well as from personal information, so that the orders had not been maximized. The educative program was conducted through counselling and couching the SMMEs. Data from pretest and posttest showed positive effects of the program. Keywords: promotion, advertisement, persuasive, packaging, culinary.